Karakterisasi Protein VirB4 Brucella abortus Isolat Lokal dengan Teknik Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis - Praja, Ratih Novita; Handijatno, Didik; Koesdarto, Setiawan; Yudhana, Aditya (Jurnal Veteriner; Vol 18 No 3 (2017), 2017)
Brucellosis is a zoonotic disease cause by pathogenic bacteria of the genus Brucella . The disease infects livestock mammals such as cows, goats, pigs, and including humans. Brucella abortus has several potential virulence factors, i.e. Proteins VirB. Type IV secretion system (T4SS) which is a combination of 12 proteins from VirB1-VirB11 and VirD4. Brucella can survive for long periods in the environment despite the limitations of nutrients and oxygen. This study aims to characterize the protein VirB4 of local isolate of B. abortus using SDS PAGE (Sodium Dodecly sulfate-polyacrylamide gel electrophoresis). The results showed that the protein contained 10 protein bands with a molecular weight of 158.93; 110.89; 99.931; 70.60; 64.61; 59.25; 45.32; 42.35; 23.63; and 16.70 kDa, respectively. Protein VirB4 of the local isolate of B. abortus have a molecular weight of 59.25 kDa. ABSTRAK Brucellosis merupakan salah satu penyakit zoonosis yang disebabkan oleh bakteri patogen genus Brucella. Penyakit ini menyerang hewan ternak mamalia seperti sapi, kambing, babi, dan dapat menular ke manusia. Bakteri Brucella abortus memiliki faktor virulensi potensial yaitu protein Vir B. Type IV Secretion System ( T4SS) merupakan gabungan dari 12 protein yaitu Vir B1– Vir B11 dan Vir D4. Brucella dapat bertahan hidup lama di dalam lingkungan meskipun memiliki keterbatasan nutrisi dan oksigen. Penelitian ini dilakukan untuk karakterisasi protein VirB4 B. abortus isolat lokal dengan metode Sodium Dodecly Sulfate-Polyacrylamide Gel Electrophoresis (SDS PAGE). Hasil karakterisasi protein B. abortus isolat lokal dengan teknik SDS-PAGE terdapat 10 pita protein dengan bobot molekul 158,93; 110,89; 99,931; 70,60; 64,61; 59,25; 45,32; 42,35; 23,63; dan 16,70 kDa. Simpulan penelitian ini adalah terdapat protein VirB4 B. abortus isolat lokal yang mempunyai bobot molekul 59,25 kDa.